Revision of Efflatouniella Kröber, 1927 (Diptera: Therevidae) - Mohammad, Salwa K.; Badrawy, Haitham B. M. (Zootaxa, 2011)
In this paper, the genus Efflatouniella Kröber is rediagnosed and redescribed with material from Egypt and Israel. Efflatouniella aegyptiaca Kröber, 1927 is redescribed while E. legaensis sp. nov. and E. sinatica sp. nov. are described from South Sinai. Keys to the Egyptian phycine genera and to species of the genus Efflatouniella are included.